Cyanopyridine based conjugated polymer-synthesis and characterization. (5th November 2015) - Hemavathi, B.; Ahipa, T.N.; Pillai, Saju; Pai, Ranjith Krishna
Abstract: Two novel D-A polymers containing pyridine with vinylene spacer, P1 andP2 were synthesised through Heck polymerisation. In both the polymers, pyridine is linked with two donor phenylene at position-4 and -6, and electron withdrawing cyano group at position-3. Additionally, P1 possess methoxy side chain at position-2 of 3-cyanopyridine andP2 is flanked with both methoxy and octyloxy side chain at alternate pyridine. The polymers are well characterised with 1 H-NMR, UV–Vis absorption, PL, GPC, TGA, cyclic voltammetry and AFM. TGA data reveal that the polymersP1 andP2 are thermally stable up to 350–400 °C. The UV–Vis absorption spectra for solid thin films envisage efficient molecular stacking with red shifting the absorption maxima to 30 nm when compared to solution. The obtained polymers have a band gap of 1.8–1.93 eV with low laying HOMO and LUMO energy level. The polymers displayed very good blue fluorescence in CHCl3 upon irradiated with UV light (254 nm) and Atomic force microscopy (AFM) applications to polymerP1 andP2 surfaces are providing interesting images of nanometre-scale polymer structures. Graphical abstract: Highlights: Two cyanopyridine based conjugated polymers, P1 andP2 were synthesised via Heck reaction. P1 andP2 have band gap of 1.83 and 1.93 eV, respectively and have lower HOMO and LUMO energy level. Both polymers exhibit fluorescence with emission of blue light when irradiated with UV light.